ESTADO NUTRICIONAL DEL ADULTO EN EL PERU - Pajuelo Ramírez, Jaime (2024)
Studies were made on 3593 persons of both sexes and over 20 years old. 67% belonged to íemale sex and 339ó to male sex. Information on weight and height wascollected. For lts analysis, the Quetelet Index (P/f2) was used, as wellasJames et. al. classification and E. Jequier's for deficit and excess respectively. In the overall country study it was found 6.3% with low weight, 3% with different levels oí chronical energetic defficiency (CED), 56.9% within the normal range and 33.9% with obesity in different ranges. The íemale sex presents higher prevalence oí ced and obesity. Highlands and jungle present higher prevalence oí CED and lesser obesity. Snme occurs with persons over 60 years. In studies carried in Metropolitan Lima, we can observe that with respect to women, height averages hnve not vnried in comparison to the study made in 1975. On the other slde the diíerence in the nutritional level oí employees vs. workers is emphasized. We conclude that corps mass index can be incorporated to a system ofíeeding and nutrltionnl vlgilance, ns it informs on the magnitude ofthe problemand its localization, which íor this case especia U y coincides with the findings forchildren oí less tban 6 years old.